Penguatan Literasi Membaca dengan Pemberdayaan Perpustakaan Mini di Tanjung Bemban - Kevin Leonardo; Claudia Stefani; Iven Julia; Hartati Lie; Ferdy Sanjaya; Sutarto Wasatan; Melly Yana; Mahfuz Hudori (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Tanjung Bamban is a village located in Batu Besar, kecamatan Nongsa, Batam City, Kepulauan Riau. At Tanjung Bemban there is a place where children learn something, but there is no library that can support their learning. The implementation method used in this program is a survey, observation, planning, and implementation. Making a small library is expected to have positive impacts on the children. Hopefully, in the future, the library that we build will become bigger so it can be more useful for the wider community.